1
$\begingroup$

I am trying to follow a guide for the method of characteristics; quoting the first example:

We use the method of characteristics to solve the problem

$ 2u_x - u_y = 0, \;\; u(x, 0) = f(x) $

(...) we can easily solve [the characteristic equations] to get:

$x = 2s + x_0 \;\;\; y= -s + y_0 \;\;\; u = u_0$

Up to here I have no problem. However, the guide then substitutes in the initial condition and says this:

we now eliminate $x_0$ and $s$ to find that:

$ y = -s \;\;\; \Rightarrow \;\;\; u = f(x_0) = f(x - 2s) = f(x + 2y)$

My question is: where did $y_0$ and $u_0$ go?

$\endgroup$
  • $\begingroup$ More simply, the method shows that for every $(x_0,y_0,s)$, $$u(x_0+2s,y_0-s)=u(x_0,y_0).$$ For every $(x,y)$, choosing $(x_0,y_0,s)=(x+2y,0,-y)$ above, one gets $$u(x,y)=u(x+2y,0).$$ Rename $u(\ ,0)$ as $f$ and you are done. $\endgroup$ – Did Feb 5 '16 at 7:35
  • $\begingroup$ @Did I.. don't quite follow. How does the method show that? $\endgroup$ – lvc Feb 5 '16 at 7:46
  • $\begingroup$ First line simply rephrases the fact that "$u$ remains constant on the curve $(x(s),y(s))$", for $x(s)=2s+x_0$, $y(s)=-s+y_0$, that is, that $u(x(s),y(s))=u(x(0),y(0))$ for every $s$. Second line is self-explanatory. What remains? $\endgroup$ – Did Feb 5 '16 at 7:49
  • $\begingroup$ @Did I think there's some deep background here that I've missed - "$u$ remains constant on the curve $(x(s), y(s))$" isn't a fact that I recognise. Where does it come from? $\endgroup$ – lvc Feb 5 '16 at 7:57
  • 1
    $\begingroup$ Lines 3-5 of the text you linked to. $\endgroup$ – Did Feb 5 '16 at 7:59
2
$\begingroup$

You have characteristics given as functions $x(s)$ and $y(s)$ which depend on parameter $s$:

\begin{align} x = x(s) &= x_0 + 2s && \implies& x_0 &= x - 2s \label{1}\tag{1} \\ y = y(s) &= y_0 - s && \implies& y_0 &= y + s \label{2}\tag{2} \end{align}

The initial condition $u\left(x_0, 0\right) = f\left(x_0\right)$ is given for $y_0=0$, so in equation $\eqref{2}$ we set $y_0$ to be equal $0$:

$$0 = y_0 = y + s \qquad\;\implies \quad\bbox[5pt, border: 1.5pt solid #DD0712]{y = -s^{\,\!}} \label{3}\tag{3}$$

But then we can write general solutions as $$ u\left(x_0, y_0\right) = u\left(x_0, 0\right) = f\left(x_0\right) = f\left(x-2s\right) \overset{\eqref{3}}{=} f\left(x+2s\right) $$


Now, one can ask why do we say that $u\left(x_0, y_0\right)$ is the general solution? Well, if you recall the definition of characteristics, which are the

$\;\big(\cdots\big)\;$ parametric curves along which solution $u\left(x, y\right)$ remains constant,

you will see that $u\left(x, y\right) = u\left(x_0, y_0\right)$ as long as $(x,y)$ and $\left(x_0,y_0\right)$ lie on the same curve $\eqref{1}$–$\eqref{2}$. Then we choose $y_0$ to be equal $0$ in order to incorporate initial condition $u(x,0) = f(x)$.

$\endgroup$
0
$\begingroup$

The characteristic equations are : $$\frac{dx}{2}=\frac{dy}{-1}=\frac{du}{0}$$ which leads to the equations of chararacteristics : $$\begin{cases}u=c_1\\x+2y=c_2 \end{cases}$$ The general solution on implicit form with is : $$\Phi\left(u\:,\:x+2y\right)=0$$ where $\Phi$ is any derivable function of two variables.

This is equivalent to : $$u=F(x+2y)$$ where $F$ is any derivable function.

The bounding condition leads to : $$u(x,0)=f(x)=F(x+0)=F(x)$$ Hense $F=f$ is now determined and the solution is : $$u(x,y)=F(x+2y)=f(x+2y)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.